ChemInform Abstract: Synthesis and Isolation of Enantiomerically Enriched Cyclopenta[b]benzofurans Based on Products from Anodic Oxidation of 2, 4‐Dimethylphenol. Issue 48 (December 2015) - Mirion, Michael; Andernach, Lars; Stobe, Caroline; Barjau, Joaquin; Schollmeyer, Dieter; Opatz, Till; Luetzen, Arne; Waldvogel, Siegfried R.
Abstract: Tetramer (I) is obtained by anodic oxidation of 2, 4‐dimethylphenol as reported in a previous paper.